Cytologic findings in stratified mucin‐producing intraepithelial lesion of the cervix: A report of 34 cases. Issue 1 (23rd October 2015) - Backhouse, Anastasia; Stewart, Colin J. R.; Koay, Mei Hui E.; Hunter, Andrew; Tran, Ha; Farrell, Louise; Ruba, Sukeerat
Abstract : Background: Stratified mucin‐producing intraepithelial lesion (SMILE) is an uncommon variant of in situ carcinoma of the cervix. This study aimed to identify the cytologic features of SMILE since these have not been well documented previously. Methods: The study group comprised 34 consecutive cases of SMILE encountered at a single institution in which a corresponding Papanicolaou smear, taken up to 12 months before histologic diagnosis, was available for review. The presence of associated cervical neoplastic lesions including cervical intraepithelial neoplasia (CIN), adenocarcinoma in situ (AIS), and invasive carcinoma was recorded. The linear extent and distribution of the SMILEs was also noted. Results: Most Pap smears had been reported to show possible or definite high‐grade CIN although 3 cases reported the presence of a high‐grade glandular abnormality. No case had a prospective cytologic diagnosis of SMILE. Histology revealed concurrent CIN and/or AIS in all cases, and 1 specimen (3%) showed invasive adenocarcinoma. Following smear review, 23 of the 31 cases that included endocervical material showed recurrent cytologic features that appeared consistent with SMILE. These included three dimensional cell clusters with nuclear stratification and crowding, mild nuclear atypia, cytoplasmic vacuoles, mitotic figures, and apoptosis. Conclusion: SMILE is almost always associated with additional HPV‐related neoplastic lesions although only one patient (3%) had invasive carcinoma, a lower rate than recorded in other studies. Consistent cytologic features associated with SMILE were identified but these were relatively subtle. However, increased awareness of these features may permit prospective diagnosis and this could influence patient management. Diagn. Cytopathol. 2016;44:20–25. © 2015 Wiley Periodicals, Inc.